Low and full dose apixaban in patients with atrial fibrillation and renal dysfunction: findings from a national registry. (14th October 2021) - Gurevitz, C; Giladi, E; Klempfner, R; Goldenberg, I; Barsheshet, A; Kornowski, R; Elis, A
Abstract: Background: The use of direct oral anticoagulants for stroke prevention in patients with non-valvular atrial fibrillation is robust. However, the efficacy and safety of different dosage in patients with renal dysfunction is still a clinical challenge. We aimed to evaluate the clinical characteristics and outcomes of patients treated with apixaban in its different doses. Methods: A multicenter prospective cohort study, where consecutive eligible apixaban or warfarin treated patients with non-valvular atrial fibrillation and renal impairment (eGFR MDRD <60 ml/min/BSA) were registered. All patients were prospectively followed-up for clinical events and dosing adjustments over a mean period of 1 year. Analyses were performed according to the dose of apixaban given, with consideration to the standard indications for dose reduction. The primary outcomes were 1 year: mortality, stroke or systemic embolism, major bleeding and myocardial infarction as well as their composite occurrence. Results: Among the study population (n=2140), the risk for composite outcome and for mortality were both significantly lower in the high dose apixaban group (n=491) than that of the warfarin group (n=976) and the low dose apixaban group (n=673, figure 1); Dosing analysis revealed Dosing analysis revealed that only 65% of the apixaban treated patients were appropriately dosed (figure 2), and 53% of the patients who were treated by low dose apixaban were under-dosed. Treatment with inappropriately under-dose apixaban was associated with improved survival rate and composite endpoint than treatment with appropriately low dose apixaban. Appropriately high dose apixaban compared to inappropriately over-dosed patients resulted in no significant difference. Overall, appropriately dosed apixaban treated patients (any dose) had better prognosis than matched warfarin treated patients. Conclusion: Apixaban at any dose is a reasonable alternative to warfarin in patients with renal impairment, possibly associated with improved outcomes. Apixaban is still largely under-dosed in patients with renal dysfunction. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Educational grant from Pfizer